(untitled) (Journal of Educational Sciences, 2017)
The article describes method of education through investigation of basic logic elements and complex methods of using and carrying out of logic function of scheme construction in the study of radio-electronics are presented. We give lab exercises, which are determined by the tasks described by the methods of their implementation. Laboratory work is performed using the simulator Electronics Workbench software. The first part is a description of Electronics Workbench (EWB) a computer program, which allows to simulate and explore a variety of basic logic circuits (both analog and digital) with a personal computer. The program uses virtual instrumentation. In the second part contains diagrams and descriptions of laboratory works, which contain material that allows students to learn independently independently collect circuit and carry out the necessary measurements, enabling them to work from home over the material of this lesson and learn to conduct their own research (including Electronics). The modern development of science and technology requires a mandatory familiarize students with the possibilities of computer modeling, which allows analysis of complex electronic devices in a short time and with minimal economic costs. Development work with EWB program allows the teacher not only to develop new laboratory work, but also an opportunity to show the work of the studied devices using conventional graphic symbols of components of electronic circuits in the process of explaining the new material. Key words: combinational circuits, oscillator slogans, clock generator, logic elements, Electronics Workbench.